1989
DOI: 10.1289/ehp.8982253
|View full text |Cite
|
Sign up to set email alerts
|

32P analysis of DNA adducts in tissues of benzene-treated rats.

Abstract: Solid tumors have been reported in the Zymbal gland, oral and nasal cavities, liver, and mammary gland of Sprague-Dawley rats following chronic, high-dose administration of benzene. The carcinogenic activity of benzene is thought to be caused by activation to toxic metabolites that can interact with DNA, forming covalent adducts. A nuclease P1-enhanced 32P-postlabeling assay, having a sensitivity limit of 1 adduct in 10(9-10) DNA nucleotides, was found suitable for measuring aromatic DNA adducts derived in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…In addition, animal studies have shown that after benzene exposure, increases in micronuclei, chromosome loss, and breakage are seen in the hematopoietic cells of mice and rats (1,4,5). These chromosomal effects, combined with observations that benzene is only weakly mutagenic in standard gene mutation assays (6,7) and binds poorly to DNA (8,9) suggest that indirect genetic mechanisms that result in translocations, deletions, aberrant recombination, or aneuploidy may be important in benzene's genotoxic effects (10,11). It is also likely that the chromosome damage seen in the blood cells of occupationally exposed populations reflects alterations occurring in the hematopoietic stem cells, which contribute to leukemogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, animal studies have shown that after benzene exposure, increases in micronuclei, chromosome loss, and breakage are seen in the hematopoietic cells of mice and rats (1,4,5). These chromosomal effects, combined with observations that benzene is only weakly mutagenic in standard gene mutation assays (6,7) and binds poorly to DNA (8,9) suggest that indirect genetic mechanisms that result in translocations, deletions, aberrant recombination, or aneuploidy may be important in benzene's genotoxic effects (10,11). It is also likely that the chromosome damage seen in the blood cells of occupationally exposed populations reflects alterations occurring in the hematopoietic stem cells, which contribute to leukemogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, the data suggest that an adducted 3'-nucleotide with a carcinogen bound to a base at the exocyclic position, but not at the endocyclic position, is resistant to nuclease P -mediated dephosphorylation. When the attachment is simultaneously at the exocyclic and endocyclic positions, for example, a cyclic adduct, as in the case of the major adduct of BQ-DNA above, the adduct may not be susceptible to the enzyme activity (21). Such differential enzyme activity may be useful in adduct characterization.…”
Section: Discussionmentioning
confidence: 99%
“…32P-postlabeling studies have demonstrated DNA adduct formation in the liver of New Zealand rabbits74) and in the bone marrow of B6C3Fi mice 75) treated with benzene ; however, Reddy et al [76][77][78] were unable to detect the formation of DNA adducts in various tissues of either Sprague-Dawley rats or B6C3Fi mice administered benzene or its hydroxylated metabolites.…”
Section: Genotoxicity (Mutagenicity)mentioning
confidence: 99%